Hip Arthroscopy With Initial Access to the Peripheral Compartment: a Detailed Step-by-Step Technique Description - Dantas, P (2021)
Hip arthroscopy with initial access to the peripheral compartment represents a specific technique to approach the hip that can be particularly useful. This technique is suitable for both the arthroscopic treatment of femoroacetabular impingement syndrome and other pathologies that can be addressed by classic arthroscopy with central compartment initial access. Minimal capsulotomies preserve the fluid pressure in the peripheral compartment, which allows the "ballooning" of the capsule and improved joint exposure with decreased risk of fluid extravasation. In the vast majority of cases, the hip joint can be accessed by any technique depending on the surgeon preference/expertise. Interestingly, access to the central compartment under direct arthroscopic visualization decreases the risk of iatrogenic labral and chondral damage. This is particularly important when access to the central compartment is technically challenging (e.g., acetabular overcoverage, labral hypertrophy, and limited joint distraction). Such a technique is also preferable if the pathology is mainly located in the peripheral compartment. Despite several advantages, hip arthroscopy with initial access to the peripheral compartment is not a commonly performed technique. Our purpose is to perform a step-by-step explanation of a previously described technique.